Clinical presentation, diagnostic investigations and follow-up of a Bengal tiger (Panthera tigris tigris) affected by ambulatory tetraparesis - Mosconi, Stefania; Morici, Manuel; Auriemma, Edoardo; Di Graci, Salvatore; Calloni, Anna; Zanna, Giordana; Tirrito, Federica (Brazilian Journal of Veterinary Medicine, 2025)
An 11-year-old male Bengal tiger (Panthera tigris tigris) was referred for a 2-week history of ambulatory tetraparesis, generalized ataxia, and hypermetric gait, associated with mild right head tilt and spontaneous proprioceptive deficit on the right forelimb. Neuroanatomical localization was C1-C5 myelopathy; cerebellum-vestibular system involvement was also considered. Hematology and serum biochemistry were unremarkable, although serum vitamin A (0.11 mg/L) was below the reference range (0.17 - 0.36 mg/L). Indirect hemagglutination test for Toxoplasma gondii was positive (antibodies titer 1:640). Computed tomography of the head and cervical column showed hypertrophic degenerative remodeling of the vertebral articular joint processes, causing severe vertebral canal stenosis and bilateral spinal cord compression at C2-C3. In addition, bilateral otitis media was present, without signs of intracranial extension of the inflammation by imaging. Brainstem auditory evoked potential test revealed a partial, bilateral conductive deafness. Cerebrospinal fluid (CSF) analysis resulted normal; CSF PCR for T. gondii was negative. A diagnosis of osseous-associated cervical spondylomyelopathy (OA-CSM) and concurrent bilateral otitis media was obtained. Glucocorticoids, movement restriction, vitamin A supplementation, and clindamycin were instituted. Four weeks later the clinical signs deteriorated, and the animal was euthanized. To the authors’ knowledge this is the first report of OA-CSM in a tiger.